METHODOLOGY OF ENGLISH LANGUAGE - Ahundjanova Mohira; Tadjibayev Isakjon (Journals Park Publishing, 2022)
Teaching methodology is a set of methods, techniques, technologies and ways of learning a language. As a rule, this is a clear algorithm of actions that will allow students to learn English from scratch to an advanced level and teachers to manage this process effectively.Tutors must be fluent in the methodological basis of teaching, because the final result of their work depends on it. In addition, knowledge of the theory is a guarantee of employment in prestigious universities, private schools and kindergartens. The following article is devoted to analyzing various methods of teaching English.
Keywords: methodology; communication; approach